Method to simulate and analyse induced stresses for laser crystal packaging technologies - Ribes-Pleguezuelo, Pol; Zhang, Site; Beckert, Erik; Eberhardt, Ramona; Wyrowski, Frank; Tuennermann, Andreas (Optics Express, 2017)
A method to simulate induced stresses for a laser crystal packaging technique and the consequent study of birefringent effects inside the laser cavities has been developed. The method has been implemented by thermo-mechanical simulations implemented with ANSYS 17.0. ANSYS results were later imported in VirtualLab Fusion software where input/output beams in terms of wavelengths and polarization were analysed. The study has been built in the context of a low-stress soldering technique implemented for glass or crystal optics packaging's called the solderjet bumping technique. The outcome of the analysis showed almost no difference between the input and output laser beams for the laser cavity constructed with an yttrium aluminum garnet active laser crystal, a second harmonic generator beta-barium borate, and the output laser mirror made of fused silica assembled by the low-stress solderjet bumping technique.
CRIS-Team Scopus Importer:2023-04-20